Beyond Content: Constructivist 7E Lessons and Emergence of Critical Thinking, Creativity, and Problem-solving in Ghanaian Senior High Electronics Studies - Innocent Kwesi Ofori; Eric Appiah-Twumasi; Kenneth Ateko Darko (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study explored how 7E-instructed lessons on electronics concepts improved 21st-century skills among Senior High School (SHS) physics students in the Birim North District, Eastern Region, Ghana. Driven by Constructivist Learning Theory, Experiential Learning Theory, and the P21 Framework for 21st-Century Skills, it focused on three questions: students’ proficiency in critical thinking, creativity and innovation, and problem-solving; the impact of 7E lessons on these skills; and the appearance of these skills in students’ post-test responses. Methodology: Using a pragmatist approach, a mixed-methods design with concurrent triangulation was employed, combining a pre-test-post-test quantitative assessment with qualitative content analysis. The study involved 103 SHS 2 physics students from two purposively chosen public schools. Main Findings: The main assessment, a 21st-Century Skills Test on Electronics Concepts, was scored with detailed, task-specific rubrics. Pre-test results indicated that all three skills were at low levels, with average scores below 2.0 on a 4-point scale, highlighting the shortcomings of traditional, teacher-centered teaching. After six weeks of the 7E instructional program, paired-samples t-tests revealed significant improvements across all skills, with large effect sizes: critical thinking (d = 0.912), problem-solving (d = 0.867), and creativity and innovation (d = 0.834). Qualitative analysis uncovered three themes in post-test responses: enhanced analytical integration, the emergence of feasible novel ideas, and structured procedural coherence. Novelty/Originality of this study: The 7E Instructional Model may be an effective, curriculum-aligned strategy for fostering 21st-century skills among Ghanaian SHS physics students in electronics.